All-trans-retinoic acid restores CD4+ T cell response after sepsis by inhibiting the expansion and activation of myeloid-derived suppressor cells. (August 2021) - Liu, Tao; Yang, Fan; Xie, Jie; Chen, Jiajun; Gao, Wei; Bai, Xiangjun; Li, Zhanfei
Highlights: ATRA reduced the mortality of secondary infection after sepsis by regulating MDSCs. ATRA restored CD4+ T cell function that was suppressed by MDSCs in sepsis. ATRA inhibited the expansion and activity of MDSCs after sepsis. Abstract: Background: Patients are susceptible to immunosuppression in late-stage of sepsis, in which myeloid-derived suppressor cells (MDSCs) is an important contributor. This study aims to investigate whether all-trans-retinoic acid (ATRA), which has been proved to inhibit MDSCs generation in cancer, will ameliorate sepsis-induced immuno-suppression through modulating MDSCs. Methods: A clinically relevant "two-hit'' model of sepsis, the cecal ligation and puncture (CLP) model and secondary pneumonia model, were established in mice. The effects of ATRA on the mortality, the bacterial burden, the expansion and activity of CLP-induced MDSCs, as well as the function of CD4+ T cells were evaluated. Results: In CLP model, ATRA was found to reduce frequency of MDSCs in spleen of mice and inhibit activity of MDSCs by regulating the generation and activity of arginase-1 and iNOS, and the secretion of immune-supressive cytokines. ATRA administration eventually reduced mortality of secondary infection by Legionella pneumophila in CLP-surviving mice, which might be associated with the restoration of CD4+ T cells proliferating and secreting activity. Conclusion: ATRA can restore CD4+ T cells dysfunction in sepsis by modulating the expansion and function of MDSCs and therefore provides a potential therapy that targets the immunosuppressive state of sepsis.